(untitled) (Bangladesh Journal of Agricultural Research, 2023)
This experiment was executed at the research field of Department of Crop Botany, Bangabandhu Sheikh Mujibur Rahman Agricultural University, Bangladesh during 2019 to 2020. In this study, methanolic extract of different plant parts was used for observing the antioxidant properties such as total phenolic, flavonoids, carotenoids and anthocyanins content in Skunk vine (P. foetida). Results showed that, the total phenolic were more or less similar in leaf (357.62 μg/g) and stem (349.42 μg/g) and that were significantly higher than that of root extract (233.56 μg/g). The highest amount of flavonoid content (602.71 μg/g) was recorded in leaf extract and the content was more or less similar in stem (493.16 μg/g) and root extracts (501.86 μg/g). Maximum amount of anthocyanin content was recorded in leaf (42.04 μg/g) that was identical with that of stem extract (39.68 μg/g) and statistically the lowest amount in root extract (27.44 μg/g). The fresh leaf extracts contained higher carotenoid content (41.96 mg/g) than stem (25.58 mg/g). Total antioxidant activity in respect to percentage of DPPH ((2,2-diphenyl-1-picrylhydrazyl) scavenging efficiency, leaf extract showed 63.78% inhibition efficiency which were significantly higher than that of stem (45.75%) and root (24.19%). α- glucosidase activity was greatly inhibited (59.13%) by leaf extract at the concentration level of 1.5 mg/mL which was better than that of stem (45.60%). Inhibition of α-amylase activity was recorded up to 46.23 and 42.57% by leaf and stem extracts, respectively which were statistically similar. The present study suggests that medicinal plant Skunk vine (P. foetida) has both antioxidative and antidiabetic properties which would be the good source for producing safe natural drugs. Bangladesh J. Agril. Res. 46(1): 1-12, March 2021